Dynamic Oscillations Evoked by Subcallosal Cingulate Deep Brain Stimulation - Tiruvadi, Vineet; Choi, Ki Sueng; Gross, Robert E.; Butera, Robert; Jirsa, Viktor; Mayberg, Helen (Frontiers in Neuroscience, 2022)
Deep brain stimulation (DBS) of subcallosal cingulate white matter (SCCwm) alleviates symptoms of depression, but its mechanistic effects on brain dynamics remain unclear. In this study we used a novel combination of intracranial (LFP) and non-invasive (EEG) neural recordings during SCCwm-DBS, and observed a novel dynamic oscillation (DOs) evoked by DBS within the SCC. When present, LFP-DOs were consistently evoked by DBS within the SCC, supporting a neural source, and exhibited dynamics evolving over minutes. LFP-DOs were associated with engagement of distinct white matter tracts, and we observed preliminary evidence that DOs are evoked in EEG recordings downstream of stimulated SCCwm under therapeutic conditions. These results provide an signal for further study of SCCwm-DBS effects and potential applications in connectomic and steerable DBS.